Scale up of community-based injectable contraceptives in Gombe State, Nigeria - Akinyemi, Oluwaseun Oladapo (My University, 2020)
Globally, many health innovations have contributed to improving the quality of life in the last few decades. These include interventions that have been used successfully to fight tuberculosis, malaria, AIDS, as well as to encourage contraceptive use among those not wishing to become pregnant. One such health innovation that has been piloted with significant success around the world, including Nigeria, is the community-based distribution of injectable contraceptives by Community Health Extension Workers (CHEWs). This innovation entails enabling CHEWs to administer injectable contraceptives which previously was administered only by nurses and doctors and taking its provision beyond the health facilities into the community. Evidence now abounds that community health para professionals can safely administer the injectable contraceptive Depo-Provera (medroxyprogesterone acetate), which is given every three months to reproductive age group women in the community who do not desire to get pregnant. This innovation has been shown to be safe and effective in demonstration projects in many African countries including Uganda, Kenya, Malawi, Ethiopia and Rwanda. Also, evidence abounds that access to family planning commodities is improved through community-based distribution (CBD) thereby giving potential users more choices with regards to the family planning methods to adopt. Although some improvement has been made in the last few years, Nigeria has not fully exploited the potential of the innovation to expand access to family planning services. Uptake of family planning interventions is particularly imperative in this setting with low contraceptive prevalence rates (CPR) – 9.7% and 14.6% for modern methods and any method, respectively - and a wide rural-urban dichotomy. Presently, only 3% of Nigerian married women use injectable contraceptives. Increasing contraceptive prevalence is a priority for Nigeria where the fertility rate, currently 6 per woman, continues to be a public health vi concern. The low CPR is a vital contributor to the country’s maternal mortality ratio which currently stands at 576/100,000 live births. Maternal deaths are responsible for approximately a third of all deaths among women of reproductive age. Although Nigeria has implemented CBD of oral contraceptives since 2003, it was only in 2007 that the country started reviewing its family planning policy. This resulted in a pilot study in 2010 in Gombe State, North-eastern Nigeria, which tested the feasibility of CHEWs dispensing injectable contraceptives at the community level. The pilot study demonstrated that CHEWs can administer injectable contraceptives safely in the community and that community-based access to injectable contraceptives was a more effective approach compared to the facility-based system. The pilot project demonstrated that the CBD approach produced a significantly higher couple of years of protection compared with the facility-based services. The pilot also shows that given the health worker shortage in the country, CHEWs can increase access to injectable contraceptives, particularly in the rural areas, in a more effective and efficient way. In low- and middle-income countries in particular, it has been shown thatscale up is necessary to make health innovations (such as CBD of injectable contraceptives) available to those who need them. Scale up ensures that proven health innovations are made available to more people, in many more locations through improved provision of human resources, financing materials and a more efficient health system. Sequel to a successful pilot in Nigeria, a decision was taken to scale up the intervention to a wider geographical area and to more users, starting with expansion to the rest of Gombe State and later spreading to other regions of the country. Scale up was planned to guarantee that the benefits of the innovation recognized in the pilot (carried out in one of the 36 states) are made available throughout the country. In 2014, a national NGO led the scale up process of the community administered injectable vii contraceptives in Nigeria. The process commenced with the training of trainers and CHEWs. However, there is inadequate understanding on how to scale up this innovation effectively outside the original pilot location, and to scale up in ways that can increase uptake and address unmet needs. Of the available scale up frameworks, the AIDED model (Assess, Innovate, Develop, Engage and Devolve) proposed by Bradley and colleagues, was adopted for this work because it captures a set of interrelated factors that may affect innovation scale up. Assess measures the receptivity of the user groups; Innovate component deals with the process of designing and packaging the innovation to fit users’ preferences while the Develop constituent entails enhancing support and addressing resistance to the innovation. The Engage component entails ensuring that the innovation is embedded in the routine practices of potential users and community members while Devolve refers to the process of spreading the innovation to newer groups.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2020